Folic acid supplementation in pregnancy related to the development of childhood neurological disorders (Research, Society and Development, 2022)
Thus, the present study aims to clarify the risk and benefit of using folic acid supplementation in the gestational period, and to clarify the consequences related to excessive use considered TEA as a psychopathology associated with high supplementation. This is an integrative review of the literature, which consists of broader methodological approaches among literature reviews. The preparation of a methodological survey for the research was carried out in the period of March 2022, the databases used were the Latin American and Caribbean Literature in Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE) 27 studies were submitted which went through the analysis of the abstracts and eligibility criteria. Studies have shown that folic acid supplementation adequately benefits both mother and baby, but current studies report that increased supplementation may generate an increased risk of developing TEA, although the research is still at an early stage in the scientific field, the field of study is developing rapidly and has provided this study with suggestive evidence on the importance of these nutrients. Thus, it was possible to identify the existence of a causal factor proven to lead to autism, believing that there are a set of factors, be it environmental, genetic, chemical or by pathologies acquired during the gestational phase.